Fluorosis, Etiology and Treatment. Epidemiological Situation in Our Region, Measures to Prevent Fluorosis - Munisovna, Khaydarova Durdona; Marjona, Babanazarova; Yasmina, Ergasheva; Bashorat, Erkinova; Karina, Kasimova (American Journal of Bioscience and Clinical Integrity, 2025)
Fluorosis is a chronic pathology of tooth enamel caused by an increased concentration of fluoride in the body. It manifests itself in the formation of spots and defects of various sizes, colors and shapes on the enamel. The disease is epidemic in nature. Dental fluorosis is common in areas with a high fluoride content in drinking water. Workers of some industrial enterprises (aluminum smelters, laser equipment, etc.) are also susceptible to the disease due to an increased concentration of fluoride compounds in the air. Causes of fluorosis Fluoride is an element that enters the body with water, vitamin supplements, food and air. It participates in the formation of tooth and bone tissue, strengthens enamel and prevents the leaching of calcium from the body. However, if a lack of fluoride increases the risk of dental caries, then an excess leads to the development of enamel fluorosis.